2017
DOI: 10.1534/g3.117.042671
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway-Centered Analysis of Pig Domestication and Breeding in Eurasia

Abstract: Ascertaining the molecular and physiological basis of domestication and breeding is an active area of research. Due to the current wide distribution of its wild ancestor, the wild boar, the pig (Sus scrofa) is an excellent model to study these processes, which occurred independently in East Asia and Europe ca. 9000 yr ago. Analyzing genome variability patterns in terms of metabolic pathways is attractive since it considers the impact of interrelated functions of genes, in contrast to genome-wide scans that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
(95 reference statements)
1
10
0
Order By: Relevance
“…We ranked the list of genes according to the estimated p -values, and applied the fast gene set enrichment analysis (FGSEA) method (available as the Bioconductor package “fgsea”; Sergushichev, 2016), for each pathway. We also conducted another Gene Set Analysis (GSA)–node-based enrichment analysis which aggregates p -values of Levene’s test by Fisher’s method (Leno-Colorado et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…We ranked the list of genes according to the estimated p -values, and applied the fast gene set enrichment analysis (FGSEA) method (available as the Bioconductor package “fgsea”; Sergushichev, 2016), for each pathway. We also conducted another Gene Set Analysis (GSA)–node-based enrichment analysis which aggregates p -values of Levene’s test by Fisher’s method (Leno-Colorado et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…In studies of genetic differences between tame and aggressive foxes, changes to serotonergic signaling accompany those of the glutamatergic system, with genetic changes often po-tentially relevant to both synapses [30,31]. Similarly, domestication of the pig appears to have involved important changes across both systems [36]. Signals of selection associated with serotonergic signaling have also been identified in a tame strain of rat and the domesticated goat [105,106].…”
Section: Resultsmentioning
confidence: 99%
“…In several of the studies cited in Table 2, signals of selection on glutamate receptor genes have been suggested as potentially important for behavioral changes during the domestication process [23,27,28,29,30,36,41]. However, such suggestions form part of broader discussion on changes to genes related to the central nervous system (CNS) under domestication, and no mechanistic details are provided.…”
Section: Dogmentioning
confidence: 99%
“…We analyzed complete genome sequence from 46 domestic and wild pigs from Asia and Europe (Leno-Colorado et al, 2017;Pérez-Enciso et al, 2017). In brief, the sampling scheme was designed to be as balanced as possible while simultaneously aiming at capturing variability within continents and within domestic status.…”
Section: Animal Sequences and Snp Resourcesmentioning
confidence: 99%
“…Here, we used 23 individuals in each of the two phylogeographic groups. The use of a previously published (Leno-Colorado et al, 2017;Perez-Enciso et al, 2017) de novo SNP identification approach from genome sequencing gave us a very high resolution analytical tool with which to scrutinize the population history and genetics of these animals.…”
Section: Introductionmentioning
confidence: 99%